Manusia Sebagai Makhluk Sosial - Fadhillah Iffah; Yuni Fitri Yasni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Humans are said to be social creatures, who always want to be in touch with others, want to know the surrounding environment and want to know what is going on within themselves, that feeling forces someone to need to communicate. As social beings and living in groups in everyday life, of course, there is no such thing as interaction and mutual communication. In relation to being social beings, humans always live together with others. Humans need each other and must interact with other humans. This is because humans cannot fulfill their daily needs alone. Humans will join with other humans to form groups to fulfill their needs and life goals, which in this case will always be in contact with other social creatures because they cannot live alone. In this case, humans are always in touch with each other whether they realize it or not to always meet the needs in their lives.